T-Cells Proliferation and Serum Cytokine levels in Type 1 Diabetic Children - Saleh, Eman Mahdi (AL-Kindy College Medical Journal, 2011)
Background: There is plenty of evidencesuggesting that involvement of several groups ofviruses in the development and / or acceleration ofType 1 Diabetes Mellitus (T1DM).Objective: To analyze the T- cell proliferation inthe presence of Coxsackie virus B5 (CVB5), Polioand Adenovirus antigens in addition to assessmentof Interferon- gamma (IFN-γ), Interleukins (IL-10and IL-6).Methods: In 60 Iraqi T1DM children with recentonset of T1DM, Lymphocyte proliferation wasanalyzed using Methylthiazol tetrazolium (MTT)assay by culturing Peripheral Blood Lymphocytes(PBLs) with Coxsackie Virus B5 (CVB5),Adenovirus, and Polio vaccine. Serum Interferon-γ,IL-10 and IL-6 were quantified by sandwichELISA.Results: No significant differences were shownin the PBL proliferative percentage in response toCon-A mitogen and tested viruses (CVB5 andAdenovirus) between T1DM and healthy controls,but it showed a significant decline in patients inresponse to Polio vaccine. Higher significant serumlevels of IFN-γ, IL-10, and Il-6 were observed inthe investigated patients compared to controls(p